Analyzing Perceptions of Nursing Technicians, Midwifery Technicians, and Nursing Specialists Regarding Factors Influencing Job Satisfaction and Staff Retention in Various Healthcare Settings in Saudi Arabia - Albannat Munayjil Sulaiman Aljameel,; Fatimah Mukhlef Saleh Alrashdi,; Tarfah Hamad A Aldhafeeri,; Amal Mukhlef Saleh Alrashdi,; Zainab Munayjil Sulaiman Aljameeli,; Afaf Hamad A Aldhafeeri,; Dalal Munawir Aldhafeeri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Purpose: This study aimed to analyze the perceptions of nursing technicians, midwifery technicians, and nursing specialists regarding factors influencing job satisfaction and staff retention in various healthcare settings in Saudi Arabia. Methods: A cross-sectional survey was conducted among 450 nursing staff (150 from each category) working in public and private hospitals using a validated questionnaire. Descriptive statistics, ANOVA, and multiple regression were used for data analysis. Results: Significant differences were found in perceived job satisfaction and intention to stay across the three nursing categories (p<0.05). Nursing specialists reported higher job satisfaction and retention than technicians. Key factors influencing job satisfaction were income, workload, professional development opportunities, and management support. Retention was significantly predicted by job satisfaction, organizational commitment, and work environment (R²=0.68, p<0.001). Conclusion: Improving income, workload, professional development, management practices, and work environment could enhance the job satisfaction and retention of nursing staff in Saudi Arabia. Targeted strategies are needed to address the specific needs of each nursing category.